MHD flow of dusty jeffrey fluid flow containing Carbon Nano Tubes (CNTs) under Influences of Viscous Dissipation and Newtonian heating - Nor Aini Naili Noor, Habib; Nur Syamilah, Arifin; Syazwani, Mohd Zokri; Abdul Rahman, Mohd Kasim (Universiti Putra Malaysia, 2024)
This current research examines the behaviour of dusty Jeffrey fluid across an inclined stretching sheet with CNTs as well as aligned magnetohydrodynamic (MHD). By utilising the proper similarity transformation variables, the governing partial differential equations (PDEs) of the problem are converted to ordinary differential equations (ODEs). Then, the numerical results are produced by using the Runge-Kutta-Fehlberg (RKF45) approach with the aid of the MAPLE software. The findings include the visual illustrations of the impacts on the velocity and temperature profiles for several pertinent parameters. It clearly shows that the decline in velocity profile of fluid phase was caused by the rise in aligned angle, ratio of relaxation to retardation times, magnetic field and fluid particle interaction parameters. Meanwhile, for every parameter that is involved excluding ratio of retardation time in the fluid, the temperature profile rises in both the fluid and dusty phases. The results of this study add a unique perspective to the existing literature by offering fresh insights on the influence of CNTs and dust particles, examining their impact on two-phase flowover an inclined stretching sheet. This understanding can be utilized in the real-time application where rapid and efficient thermal management is critical such as electronics cooling or energy conversion systems. Furthermore, the inclusion of viscous dissipation andNewtonian heating (NH) effects contributes to the novelty of the research, providing a comprehensive understanding of the complex interactions in this unique fluid flow scenario.